Potential of Polyamide Nanofibers With Natamycin, Rosemary Extract, and Green Tea Extract in Active Food Packaging Development: Interactions With Food Pathogens and Assessment of Microbial Risks Elimination - Lencova, Simona; Stiborova, Hana; Munzarova, Marcela; Demnerova, Katerina; Zdenkova, Kamila (Frontiers in Microbiology, 2022)
Increasing microbial safety and prolonging the shelf life of products is one of the major challenges in the food industry. Active food packaging made from nanofibrous materials enhanced with antimicrobial substances is considered a promising way. In this study, electrospun polyamide (PA) nanofibrous materials functionalized with 2.0 wt% natamycin (NAT), rosemary extract (RE), and green tea extract (GTE), respectively, were prepared as active packaging and tested for the food pathogens Escherichia coli, Listeria monocytogenes, Salmonella enterica, and Staphylococcus aureus. The PAs exhibited: i) complete retention of bacterial cells reaching 6.0 – 6.4 log10removal, ii) antimicrobial activity with 1.6 – 3.0 log10suppression, and iii) antibiofilm activity with 1.7 – 3.0 log10suppression. The PAs prolonged the shelf life of chicken breast; up to 1.9 log10(CFU/g) suppression of total viable colonies and 2.1 log10(CFU/g) suppression of L. monocytogenes were observed after 7 days of storage at 7 °C. A beneficial effect on pH and sensory quality was verified. The results confirm microbiological safety and benefits of PA/NAT, PA/RE, and PA/GTE and their potential in developing functional and ecological packaging.